The Analysis Of Sales Promotion Towards Sales At Pt. Multimas Nabati Asahan Medan - Eddy; Susanto; Felix Leonardi; Benny Lim; Elyzabeth Wijaya (Universitas Muhammadiyah Palu, 2025)
Promotion is an activity in communicating information from sellers to buyers or other parties in the promotion to influence of the buyers. The main duty of a marketing manager in promotion is to inform customers about the products’ benefit that will be obtained by the customers if they purchase the product. Companies can use premiums, price off deals, rebates in the market. Promotion is done by a company in order to increase the company’s sales. The main thing that must be considered when doing promotion is to sell out the products as much as possible. PT. Multimas Nabati Asahan also uses promotion to improve their sales. The promotions that they use are premiums, price off deals, and rebates. In order to get data, the writer distributed a questionnaire to 30 customers. The questions consist of 10 questions, and are divided into two parts, 5 questions related to sales promotion and 5 questions related to sales. After obtaining feedback from the customers, the writer tabulated the data and analyzed it by using correlation formula, linear regression, and test hypothesis. Then, the result of the data analyzed will determine whether the hypothesis can be accepted or rejected. The result that the writer obtained is that sales promotion has an effect at PT. Multimas Nabati Asahan and is impacting the sales. At least, writer has made some conclusion from the analysis and evaluation done systematically. Some conclusions are: From the result of Coefficient Correlation between variable X and variable Y, the result was 0.84 Furthermore, the effect of sales promotion towards sales resulted in 70.56%.; it means the effect of sales promotion towards sales is affected 70.56% , which means that there is a strong relationship or positive correlation between sales promotion toward sales. Moreover, using hypothesis test the tcount is 15.10 Then, based on the distribution table t we will have the value of t with degree of freedom = 28, ? = 5%, thus ttable; dk=28; ?=0.05 = 1.701. Because tcount > ttable, we can conclude that “There is an impact of sales promotion toward sales at PT. Mulitmas Nabati Asahan Medan